2018
DOI: 10.1371/journal.pone.0207292
|View full text |Cite
|
Sign up to set email alerts
|

eHealth for people with multimorbidity: Results from the ICARE4EU project and insights from the “10 e’s” by Gunther Eysenbach

Abstract: BackgroundPeople with multimorbidity, especially older people, have complex health and social needs, and require an integrated care approach. In this respect, eHealth could be of support. This paper aims to describe the implementation of eHealth technologies in integrated care programs for people with multimorbidity in Europe, and to analyse related benefits and barriers according to outcomes from ICARE4EU study and within the more general conceptual framework of the “10 e's” in eHealth by Gunther Eysenbach.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 94 publications
0
20
0
1
Order By: Relevance
“…We identified six RCTs eligible for inclusion in the review, reported in seven publications (Wakefield (2011) 1 and Wakefield (2012) 2 reported different outcomes of the same trial) ( table 1 ). No other eligible study designs were identified (detailed characteristics of included studies in online supplemental appendix C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified six RCTs eligible for inclusion in the review, reported in seven publications (Wakefield (2011) 1 and Wakefield (2012) 2 reported different outcomes of the same trial) ( table 1 ). No other eligible study designs were identified (detailed characteristics of included studies in online supplemental appendix C ).…”
Section: Resultsmentioning
confidence: 99%
“…3 Digital telemedicine interventions have in recent years increasingly been recognised as a useful tool that could help integrate and improve care for the complex health and social needs of multimorbid patients, for example, by 'encouragement of a new relationship between patient and health professional, enabling standardised information exchange between providers, and extending the scope of healthcare in a geographical and conceptual sense'. 2 Most digital health research, however, has focused Strengths and limitations of this study ► Multimorbidity is an increasing global challenge and digital health solutions could contribute to improving care. ► Despite the attention given to digital health, no systematic review of digital health interventions for multimorbidity has been conducted before.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, the adoption of ICTs in health services and processes can innovate the provision of care at distance [19,20], especially useful for older people living in the community [21,22]. ICT has also been identified as a crucial enabler for supporting information sharing across health professionals [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Since earlier definitions [912], more recent attempts to scope digital health innovation ecosystems illustrate the growing breadth of eHealth [1315]. This simple term can encapsulate e-health, m-health (sometimes viewed as a subset of eHealth), medicine 2.0, telemedicine and telecare, public health surveillance, personalized medicine/patient engagement, health and medical platforms, self-tracking (the quantified self), wireless health and sensors, medical imaging, healthcare information systems, mobile connectivity, social networking, sensors and wearables, gamification, electronic health records, big data, health information technology, health analytics, and digitized health systems.…”
Section: Introductionmentioning
confidence: 99%